Professional Knowing in Accounting: Navigating Complexity Through Connective Practices - Dugal, Léa (Université d'Ottawa | University of Ottawa, 2025)
In recent years, Chartered Professional Accountants (CPAs) have had to cope with changes in auditing standards and regulations while keeping their workforces informed about the increasingly complex financial accounting standards (Westermann et al., 2015). When envisioning a CPA, one might picture an individual skilled at applying accounting standards to ensure accurate financial reporting. However, this thesis reveals a very different story: navigating accounting standards has become so complex that not all CPAs can manage it, and even those who can often struggle to do so comprehensively on their own. Consequently, many accountants now specialize in increasingly narrow areas of accounting standards. This thesis examines how preparers and auditors of financial statements navigate this complexity, underlining the collective and relational processes that underpin professional knowing. Drawing on McMurtry et al.’s (2016) sociomaterial framework of professional knowing, the study reveals how accountants rely on connective practices—interactions with networks of diverse expertise and material elements—to cope with the fragmentation of expertise within the profession. Through qualitative analysis of interview data with Canadian CPAs, this research emphasizes the importance of professional knowing as a collective process that extends beyond individual mastery. Complexity has led to specialization not only in ancillary fields, such as actuarial services or IT, but also within the very core of accounting knowledge itself. Accountants increasingly rely on relationships, trust, and coordination across knowledge boundaries to apply intricate standards effectively. This underscores the rise of connective professionalism (Noordegraaf, 2020), where expertise is distributed and professional work is sustained through interactional and networked practices. Taken together, these findings advance both theoretical and practical knowledge. Theoretically, they offer new insights into how professional knowing operates as a relational, adaptive process that transcends individual expertise. Practically, they provide valuable understanding for accounting professionals navigating the increasing complexity of their work, highlighting the need for continuous collaboration and the development of connective practices. By illuminating the interconnected roles of preparers and auditors, this thesis calls for a re-evaluation of professional responsibilities, regulatory expectations, and educational frameworks. The findings bear broader implications for professions adjusting to growing complexity, showcasing the transformative potential of connective practices in maintaining expertise within dynamic and challenging environments.
Keywords: Professional Knowing; Accounting standards complexity; IFRS; Connective professionalism; Connective practices; Sociomaterial; Accounting standards; Accounting profession